Estudo sobre as respostas diferenciadas de 3 espécies de roedores à fragmentação da Mata Atlântica, utilizando uma abordagem integrativa do balanço hídrico - Castellar, Alexandre [UNESP] (2015)
The use of concepts and metodologies of Phisiology to analise conservation issues has long history, and its approach goes further than describing response patterns, including also detailed comprehention of the mechanistic factors underlying conservations problems. Fragmentation and degradation of habitat result in changes on the physical environment, which directly affect physiological traits assotiated with water balance. Animals that inhabit these highly modified environments might be under water stress, and for those animals, using traits of water balance as a measure of physiological capacity for maintening homeostasis is of great value. Studies of the effects of the Atlantic Forest fragmentation on the abundance and richness of rodent species show the existence of differential response to fragmentation. This thesis addresses these patterns of responses under an integrative perspective through the analisis of parameters associated to the maintenence of water balance, and in order to provide evidences about the possible mechanistics causes of these responses. For that we used a classical protocol of water deprivation, added to the effects of temperature and to the comparison among different populations from habitats with distinct climate characteristics. The results suggest that the species Akodon montensis, Euryorysozomys russatus and Oligoryzomys nigripes hold different tolerances to water deprivation, and these differences might be related to the physiological plasticity intrinsic of each species. The analisis of the components involved in water balance revealed differences between A. montensis and E. russatus, the first one presenting a higher plasticity on the evaluated traits, which result on higher tolerance to water deprivation. Added to water deprivation, the rising of temperature induced a series of alterations on the evaluated parameters in A. montensis, imposing higher pressure on the water balance maintenance, triggering ...